Trichomycterus argos (Teleostei: Siluriformes: Trichomycteridae), a new species from the Doce River Basin, Eastern Brazil - Lezama, Antônio Queiroz; Triques, Mauro L.; Santos, Patrícia S. (Zootaxa, 2012)
Trichomycterus argos, new species, is described from the Rio Doce basin, situated in the Serra do Brigadeiro (part of theSerra da Mantiqueira) range, southeastern Brazil. The new species is diagnosed by the following characteristics: presenceof six branched rays in the pectoral fin; presence of pelvic fins; tip of nasal barbels extending to posterior border of oper-cular plate of odontodes; presence of a large foramen for ramus lateralis accessorius facialis, visible in dorsal view, in theparietosupraoccipital bone; transverse and straight border between the parietosupraoccipital and frontal bones; pectoral-fin ray prolonged as a filament; body covered with spots that seldom attain eye diameter; pelvic-fin origin placed one or two ocular diameters anterior to dorsal-fin origin; abscence of spots fused as elongated marks on dorsum or flank.